DATA LAKEHOUSE EVOLUTION: A FRAMEWORK FOR IMPLEMENTING DOMAIN-DRIVEN DATA MESH ARCHITECTURE IN ENTERPRISE SYSTEMS - Dorai Surendar Chittoor (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Modern enterprises face significant challenges in managing and scaling their data infrastructure while ensuring interoperability across diverse platforms. This article presents a comprehensive framework for implementing a Data Lakehouse architecture incorporating Data Mesh principles and leveraging serverless cloud infrastructure. The proposed approach addresses critical challenges in enterprise data management by combining domain-oriented ownership with federated governance while maintaining global data quality and interoperability standards. The implementation framework integrates open-source technologies and standardized formats to ensure platform independence and prevent vendor lock-in while adopting serverless infrastructure to optimize operational costs and scalability. Through a detailed case study, the article demonstrates how this architecture enables organizations to effectively manage distributed data systems while reducing data duplication and improving time-to-insight. The results indicate significant improvements in data accessibility, reduced operational overhead, and enhanced analytical capabilities. This article contributes to the field by providing a practical blueprint for organizations transitioning to modern data architectures, emphasizing maintaining a balance between decentralized ownership and centralized governance. The framework's effectiveness is validated through real-world implementation, offering valuable insights for practitioners and researchers in enterprise data management.